Training healthcare professionals as moral case deliberation facilitators: evaluation of a Dutch training programme. Issue 10 (26th July 2012) - Plantinga, Mirjam; Molewijk, Bert; de Bree, Menno; Moraal, Marloes; Verkerk, Marian; Widdershoven, Guy A M
Abstract : Until recently, moral case deliberation (MCD) sessions have mostly been facilitated by external experts, mainly professional ethicists. We have developed a train the facilitator programme for healthcare professionals aimed at providing them with the competences needed for being an MCD facilitator. In this paper, we present the first results of a study in which we evaluated the programme. We used a mixed methods design. One hundred and twenty trained healthcare professionals and five trainers from 16 training groups working in different healthcare organisations throughout the Netherlands were included. After completion of the programme, participants feel sufficiently confident and equipped to facilitate an MCD session. Feeling competent does not mean that participants have no doubts or questions left. Rather, they are aware of their limitations and see the need for continuous learning. According to the respondents, the actual exercise of facilitating MCD during and in between the training sessions contributed most to the development of competences necessary for being an MCD facilitator. Respondents without prior experience of participating in MCD sessions felt less competent after the training than those who had participated in MCD sessions before. Self-attributed competence varied between participants with different professional backgrounds.